COMERCIALIZAÇÃO DAS CARNES DE QUELÔNIO E JACARÉ NO MARAJÓ, PARÁ-BRASIL - SOUSA, Cleize Miranda de (2024)
The present study aimed to evaluate the consumption of turtles and alligators in the municipality of Breves, located in the Marajó archipelago, Pará, Brazil. The methodology involved the application of a questionnaire to visitors of the local municipal market. A total of 50 people participated in the survey during July and August 2019. The results indicated a trade in Amazon turtles (Podocnemis expansa), tortoises (Geochelone carbonaria and Geochelone denticulata), perem (Rhinoclemmys punctularia), muçuã (Kinosternon scorpioides), and tracajá (Podocnemis unifilis), as well as the tinga caiman (Caiman crocodilus). Consumers expressed agreement that raising these animals could prevent their extinction and ensure their availability for future generations. We conclude that cheloniculture and jacariculture could serve as alternatives for consuming these species, alongside efforts in environmental education and stricter market inspections in Breves.